If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x-3=16x-68
We move all terms to the left:
9x-3-(16x-68)=0
We get rid of parentheses
9x-16x+68-3=0
We add all the numbers together, and all the variables
-7x+65=0
We move all terms containing x to the left, all other terms to the right
-7x=-65
x=-65/-7
x=9+2/7
| 5x−12=3⋅(x−2) | | 3x-5+8(x-1)=2x+0,5 | | 6(x+2)=27 | | -56-8n=9+9n | | 2a-5/3+2a+5/15=a-3/5 | | 2(5a+1)+2=3(a-1) | | 11,8+6,6x-2,4=121,6 | | 4a-5=36 | | -8-5v=8v+6 | | 3z+12=4z-4 | | 6w+4=3w+31 | | 4m^2-4m+8=0 | | 3y+11=2y-2 | | -65-8n=4+7n | | 9z/5=-81 | | -4-4v=7v+9 | | 8z+7=7z-5 | | 3(4w+5)/4=1 | | 3x-1=23x | | 8w+5=7w+35 | | 3-3=4x-6 | | 8y+5=7y-15 | | 63,1-3x-10,5=46,6 | | 6n+8=2n+37 | | 63,1-3x10,5=46,6 | | 5,9x-6,9+2,1x=57,1 | | 8x-18=9x+3 | | 4x+-3=29 | | 530.66=3.14×(r×r) | | 5s-44=66 | | 3z/7+2=-2 | | 0=20-5(n-1) |